The art of power : my story as America's first woman Speaker of the House - Pelosi, Nancy, 1940- (Simon & Schuster, 2024)
"The most powerful woman in American political history tells the story of her transformation from housewife to House Speaker--how she became a master legislator, a key partner to presidents, and the most visible leader of the Trump resistance"--